2007
DOI: 10.1002/jcu.20358
|View full text |Cite
|
Sign up to set email alerts
|

Color doppler sonographic analysis of uterine and ovarian artery blood flow in women with polycystic ovary syndrome

Abstract: Doppler sonography of the utero-ovarian circulation may contribute to the evaluation of PCOS patients and a better understanding of the pathophysiology of this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 41 publications
1
21
1
1
Order By: Relevance
“…Abnormal uterine blood flow has been observed in women with PCOS4, 5 as well as in the subfertile population in general6, 7 and in women with idiopathic recurrent miscarriage8–10. Uterine blood flow in women with PCOS may be associated with the phenotypic expression of the disease and it has been suggested to be reduced in women with PCOS who have hyperandrogenism or are obese11, 12, although this relationship was not confirmed in other studies13, 14. This discrepancy could relate to inconsistencies in the diagnostic criteria used to define this heterogeneous endocrine disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal uterine blood flow has been observed in women with PCOS4, 5 as well as in the subfertile population in general6, 7 and in women with idiopathic recurrent miscarriage8–10. Uterine blood flow in women with PCOS may be associated with the phenotypic expression of the disease and it has been suggested to be reduced in women with PCOS who have hyperandrogenism or are obese11, 12, although this relationship was not confirmed in other studies13, 14. This discrepancy could relate to inconsistencies in the diagnostic criteria used to define this heterogeneous endocrine disorder.…”
Section: Introductionmentioning
confidence: 99%
“…27 Stromal vascularity is significantly higher in women with PCOS who are hyperandrogenic and lean rather than normoandrogenic and obese. 28 Fertile controls and PCOS women had similar total ovarian 3D power Doppler flow indices. Normal weight PCOS women had significantly higher total ovarian 3D power Doppler flow indices than their overweight counterparts.…”
Section: Stromal Vascularity In Pco and Its Hormonal Implicationsmentioning
confidence: 76%
“…Ovarian vascularity can be assessed subjectively through the application of color or power Doppler maps or objectively by measuring flow velocity and the resistance to flow with pulsed‐wave Doppler. Several authors have suggested that the blood flow to and within a polycystic ovary is increased by demonstrating reduced impedance to flow in the ovarian artery and dominant vessel within the stroma in women with PCOS64, 65, although these findings have not been confirmed by other groups66. Quantitative 3D power Doppler angiography facilitates the assessment of total blood flow within a defined volume of interest, allowing the objective assessment of total vascular flow within an organ or a specified volume of tissue41, 42.…”
Section: What Are We Trying To Identify On Ultrasound: What Exactly Imentioning
confidence: 90%